Teaching Of histological slides preparation technique at first degree level - Mohamed Ali, M. (2011)
Besides the skill to analyse histological slides, another important component of the teaching of histology is the preparation of the histological slides. The Bachelor degree programme of Biohealth Science, Universiti Malaya requires majoring students to learn the preparation of histological slides by employing the Haematoxylin and Eosin (Harris) (H&E) staining technique. This common histological method is taught in five practical sessions from a total of 14 practical sessions taught in a second year histology course During the first practical session, each student starts with the abstraction of a chosen sample. This is immediately followed by fixation of the sample by immersion in 10°'0 formalin I ext few weeks would involve dehydration process of sample in a series of alcohol with increasing concentration and paraffin infiltration (2"d week), paraffin tissue embedding (3"d week), tissue sectioning and mounting of tissue sections onto slides (41h week) and finally taining (51h week). Haernatoxylin will stain the nucleus bluish purple color while Eosin will stain the C) toplasm pinkish red Eventually, cover lips are mounted onto the surface of the stained sections using Canada Balsam as medium Each of the session is completed within a 3 hour teaching practical session with a group of facilitators as isting when necessary Some of the activities are carried out in group while some are performed individually b) each student The slide prepared are evaluated with feedbacks given so as to enable the students to use this acquired hands-on laboratorv skill immediately in final year research projects or during industrial training in suitable laboratory